2015
DOI: 10.1021/jf505584m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Inhibitory Mechanism of Kaempferol on Xanthine Oxidase

Abstract: Xanthine oxidase (XO), a key enzyme in purine catabolism, is widely distributed in human tissues. It can catalyze xanthine to generate uric acid and cause hyperuricemia and gout. Inhibition kinetics assay showed that kaempferol inhibited XO activity reversibly in a competitive manner. Strong fluorescence quenching and conformational changes of XO were found due to the formation of a kaempferol-XO complex, which was driven mainly by hydrophobic forces. The molecular docking further revealed that kaempferol inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 231 publications
(133 citation statements)
references
References 49 publications
7
124
0
2
Order By: Relevance
“…(2)-(4), the values of K i and a were calculated to be (1.31 ± 0.03) Â 10 À5 mol L À1 and 5.75 ± 0.02 (n = 3), respectively, which confirmed that kaempferol tended to be more easily and firmly bound to the free a-glucosidase rather than the a-glucosidase-sub strate complex (Phan et al, 2013;Zhang, Chen, Song, & Xie, 2006). Furthermore, the replots of slope and Y-intercept versus the concentration of kaempferol were linearly fitted, suggesting that this inhibitor had a single inhibition site or a single class of inhibition site on a-glucosidase (Wang et al, 2015). This result was consistent with that of above fluorescence titrations.…”
Section: Kinetic Type Of Inhibitionmentioning
confidence: 56%
See 1 more Smart Citation
“…(2)-(4), the values of K i and a were calculated to be (1.31 ± 0.03) Â 10 À5 mol L À1 and 5.75 ± 0.02 (n = 3), respectively, which confirmed that kaempferol tended to be more easily and firmly bound to the free a-glucosidase rather than the a-glucosidase-sub strate complex (Phan et al, 2013;Zhang, Chen, Song, & Xie, 2006). Furthermore, the replots of slope and Y-intercept versus the concentration of kaempferol were linearly fitted, suggesting that this inhibitor had a single inhibition site or a single class of inhibition site on a-glucosidase (Wang et al, 2015). This result was consistent with that of above fluorescence titrations.…”
Section: Kinetic Type Of Inhibitionmentioning
confidence: 56%
“…The replots of slope and Y-intercept versus [I] were linearly fitted, which suggested that there may be a single inhibition site or a single class of inhibition site (Wang, Zhang, Pan, & Gong, 2015). The kinetic data were analyzed using a computer program for linear regressions (Origin 8.0).…”
Section: Determination Of Inhibitory Typementioning
confidence: 99%
“…10 Molecular Modeling. The molecular docking studies were carried out by the MGL tools 1.5.6 with AutoGrid4.0 and AutoDock4.0.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Fluorescence quenching is a classical method to address such issue and has been widely used for probing the structure-affinity relationship in bindings of drugs to proteins [26,27]. It is particularly useful to explore the inhibitory mechanism of inhibitors on enzymes [28].…”
Section: Introductionmentioning
confidence: 99%